Keragaman Gen BG1 sebagai Kandidat Gen Penciri Ketahanan Penyakit pada Calon Galur Ayam IPB-D2 - N. N. Miraj; C. Sumantri; S. Murtini; N. Ulupi (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
The BG1 gene is a disease resistance candidate gene in chicken, which is located in the MHC region. The mechanism of the BG1 gene is known as an inhibitor of T lymphocyte cell activation. This study aims to identify the diversity of the SNP gene BG1 in the IPB-D2 chicken line. IPB-D2 chicken is a candidate for a new line from a cross from IPB-D1 chicken, which was selected for high body resistance and good productivity. A total of 27 DNA samples of IPB-D2 (G0) chickens and 58 samples of IPB-D2 (G2) chickens were sequenced to identify the diversity of BG1 genes. The study found 6 point mutations (g.4489 G>T, g.4712 C>T, g.4741 T>C, g.4747 T>C, g.4749 T>C, g.4761 G>A) and deletion of 2 nucleotide bases g.4758 - g.4759 delAT. The combination of 6 SNPs forms 4 haplotypes. The SNPs that changed the amino acid composition were SNP g.4489 G>T cys> phen, g.4712 C>T gln>codon stop, g.4749 T>C val>ala and g.4761 G> A gly> glu. All mutations are classified as polymorphic, low heterozygosity value, and not in Hardy-Weinberg equilibrium.